2005
DOI: 10.1136/bjo.2004.056614
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of four methods of tonometry: method agreement and interobserver variability

Abstract: Aim: To compare the inter-method agreement in intraocular pressure (IOP) measurements made with four different tonometric methods. Methods: IOP was measured with the Goldmann applanation tonometer (GAT), Tono-Pen XL, ocular blood flow tonograph (OBF), and Canon TX-10 non-contact tonometer (NCT) in a randomised order in one eye of each of 105 patients with ocular hypertension or glaucoma. Three measurements were made with each method, and by each of two independent GAT observers. GAT interobserver and tonometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
149
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(180 citation statements)
references
References 29 publications
24
149
3
1
Order By: Relevance
“…The authors presented estimates of IOP differences between tonometry methods at various levels of IOP, as in the current investigation. Of note, at 15 mm HgFapproximately the mean IOP in the current studyFestimated GAT-IOPg agreement in this study was superior to agreement between GAT and all other IOP measurement techniques considered by Tonnu et al Moreover, this study determined a mean difference of 0.1 mm Hg between GAT and IOPg values, compared with 0.7 mm Hg between GAT and NCT in the study by Tonnu et al 25 In addition, in two separate studies, Jorge et al 27 demonstrated a difference of 0.1 mm Hg between GAT and NCT values among normal 26 and glaucomatous subjects using the same NCT machine. However, using a different NCT machine (from the same manufacturer) to study the same cohort of normal subjects, the investigators reported a mean GAT-NCT difference of 0.8 mm Hg.…”
Section: Discussionmentioning
confidence: 64%
“…The authors presented estimates of IOP differences between tonometry methods at various levels of IOP, as in the current investigation. Of note, at 15 mm HgFapproximately the mean IOP in the current studyFestimated GAT-IOPg agreement in this study was superior to agreement between GAT and all other IOP measurement techniques considered by Tonnu et al Moreover, this study determined a mean difference of 0.1 mm Hg between GAT and IOPg values, compared with 0.7 mm Hg between GAT and NCT in the study by Tonnu et al 25 In addition, in two separate studies, Jorge et al 27 demonstrated a difference of 0.1 mm Hg between GAT and NCT values among normal 26 and glaucomatous subjects using the same NCT machine. However, using a different NCT machine (from the same manufacturer) to study the same cohort of normal subjects, the investigators reported a mean GAT-NCT difference of 0.8 mm Hg.…”
Section: Discussionmentioning
confidence: 64%
“…30 Goldberg 31 commented that in patients with TO, central corneal thickness is a confounder for accurate tonometry, and that apparent changes in IOP could be simply due to increases in CCT. By contrast, we found that orbital decompression did not significantly affect CCT, so would dispute this theory, but acknowledge that CCT is important in determining whether or not to commence ocular anti-hypertensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated that tonopen tends to overestimate low IOPs and underestimate high IOPs [7,8,9,10]. Others have concluded that there is no such variation [11,12].…”
Section: Indirectmentioning
confidence: 99%